1999
DOI: 10.1161/01.cir.100.17.1798
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of a Tilt Training Program for the Prevention of Refractory Neurocardiogenic Syncope in Adolescents

Abstract: Orthostatic training was found to significantly improve symptoms of adolescents with neurocardiogenic syncope unresponsive to or intolerant of traditional medications. Twice-a-day training sessions of 40 minutes were well accepted by patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
3
4

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(93 citation statements)
references
References 20 publications
4
81
3
4
Order By: Relevance
“…More recently, Di Girolamo et al reported the results of a controlled study of a tilt-training program consisting of two 40-min sessions daily for about 18 months in adolescents. 13) In that study, syncope was re-induced by tilt-testing in a single out of 24 patients (4.2%) after one month of tilt training, in contrast, to 18 out of 23 control patients (73.9%). In addition, over a mean follow-up of 18:2 AE 5:3 months, none of the 24 tilttrained patients (0%) versus 13 of 23 control patients (56.5%) had spontaneous recurrences of syncope.…”
Section: Home Orthostatic Self-trainingmentioning
confidence: 85%
See 2 more Smart Citations
“…More recently, Di Girolamo et al reported the results of a controlled study of a tilt-training program consisting of two 40-min sessions daily for about 18 months in adolescents. 13) In that study, syncope was re-induced by tilt-testing in a single out of 24 patients (4.2%) after one month of tilt training, in contrast, to 18 out of 23 control patients (73.9%). In addition, over a mean follow-up of 18:2 AE 5:3 months, none of the 24 tilttrained patients (0%) versus 13 of 23 control patients (56.5%) had spontaneous recurrences of syncope.…”
Section: Home Orthostatic Self-trainingmentioning
confidence: 85%
“…[12][13][14][15][16][17] Ector et al first described, in 1998, the continuation of a repetitive tilt-training program, consisting of one or two 30-min sessions daily, in 13 patients with neurocardiogenic syncope diagnosed with head-up tilt testing, who remained free of recurrences over a mean follow-up of 7.2 months. 12) They attributed the effects of tilt training to the repetitive and prolonged exposure of the cardiovascular system to gravitational stress, which might have a similar therapeutic effect in patients presenting with orthostatic intolerance.…”
Section: Home Orthostatic Self-trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…20 For patients with frequent episodes, orthostatic tilt training may be useful. 21 Because no single large, randomized study has been undertaken to evaluate the best treatment options for NMS, medical therapy is based on a number of small, mostly nonrandomized clinical studies. Drug studies are hampered by the unpredictable nature of the syncopal episodes.…”
Section: Treatmentmentioning
confidence: 99%
“…De facto, Ector et al 7 mostraram que a exposição repetida e prolongada do sistema cardiovascular a estímulos ortostáticos proporcionava um efeito terapêutico em doentes com síncope reflexa. A eficácia do tilt training tem sido avaliada em vários estudos observacionais, não aleatorizados [8][9][10] , mas os resultados obtidos têm sido contraditórios, dependendo muito do protocolo de treino e, essencialmente, da adesão dos doentes. Os seus mecanismos de ação são globalmente desconhecidos, pensando-se que possam estar envolvidos não só a dessensibilização dos recetores cardiopulmonares ao ortostatismo mas, também, mecanismos de remodelagem autonómia e da atividade barorreflexa.…”
Section: Introductionunclassified